Synthesis and Biological Evaluation of Tricyclic Guanidine Analogues of Batzelladine K for Antimalarial, Antileishmanial, Antibacterial, Antifungal, and Anti‐HIV Activities. (28th March 2013) - Ahmed, Nafees; Brahmbhatt, Keyur G.; Khan, Shabana I.; Jacob, Melissa; Tekwani, Babu L.; Sabde, Sudeep; Mitra, Debashis; Singh, Inder P.; Khan, Ikhlas A.; Bhutani, Kamlesh K.
<x xml:space="preserve">Abstract</x> Fifty analogues of batzelladine K were synthesized and evaluated for in vitro antimalarial (Plasmodium falciparum), antileishmanial (Leishmania donovani), antimicrobial (panel of bacteria and fungi), antiviral (HIV‐1) activities. Analogues 14h and 20l exhibited potential antimalarial activity against chloroquine‐sensitive D6 strain with IC50 1.25 and 0.88 μm and chloroquine‐resistant W2 strain with IC50 1.64 and 1.07 μm, respectively. Analogues 12c and 14c having nonyl substitution showed the most potent antileishmanial activity with IC50 2.39 and 2.78 μm and IC90 11.27 and 12.76 μm, respectively. Three analogues 12c, 14c, and 14i were the most active against various pathogenic bacteria and fungi with IC50 < 3.02 μm and MIC/MBC/MFC <6 μm. Analogue 20l having pentyl and methyl substituents on tricycle showed promising activities against all pathogens. However, none was found active against HIV‐1. Our study demonstrated that the tricyclic guanidine compounds provide new structural class for broad spectrum activity.